Circovirus Rep evades immune restriction by disrupting cGAS oligomerization and phase separation. - Hongyan Yin; Zhenchao Zhao; Ye Yuan; Minjie Li; Lvye Chai; Weiyu Qu; Yan Ya; Haiwei Wang; Xin Li (PLoS Pathogens)
Cyclic GMP-AMP synthase (cGAS) is a key sensor of double-stranded DNA (dsDNA), initiating oligomerization and phase separation to drive immune responses against pathogens and endogenous damage. Porcine circovirus (PCV) induces immunosuppression, heightening susceptibility to secondary infections, but the underlying mechanisms remain unclear. Here, we report PCV type 2d (PCV2d) infection fails to induce type I interferons (IFN-I) and significantly suppresses IFN-I production upon poly (dA:dT) stimulation in a dose-dependent manner. Mechanistically, the replication-related protein (Rep) proteins of PCV2, PCV3 and PCV4 inhibit cGAS-mediated IFN-I induction by competitively binding dsDNA, thereby disrupting cGAS oligomerization and phase separation. Interestingly, Rep also suppresses mitochondria DNA-induced cGAS activation. We further identify Rep residues Q12 and R199-W202 as key regions facilitating dsDNA binding. Our findings reveal a previously unrecognized mechanism by which circovirus Rep antagonizes cGAS activation, providing new insights into PCV-induced immunosuppression.